PENGENALAN LITERASI KEUANGAN UNTUK MENINGKATKAN DAYA SAING PEMUDA KARANG TARUNA DESA TAJAU PECAH - Bandi, Maulida Hirdianti; Karolina, Karolina; Abdillah, M. Riduan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2021)
Improving financial literacy is an urgent need in building a society that is economically strong, independent and stable. Effective financial literacy education and programs can help individuals, especially youth, understand and manage their finances better and improve overall financial well-being. The community service carried out by the Politeknik Negeri Tanah Laut Accounting Study Program is an event to help the young people of Tajau Pecah village understand financial literacy. This service is expected to be carried out regularly and can be carried out for longer, namely in several meetings, both socialization and other training so that there is more focus in the training. This activity is also expected to improve the quality of human resources, especially in Tanah Laut Regency.